Clean Water Quality Analysis based on Chemical Parameters at the Taha Qur’an Education Park Bima Regency - Azwaruddin, Azwaruddin; Abdullah, Taufik; Wahyuningsih, Sri (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Unclean water is the cause of skin diseases. Skin diseases are included in water washed diseases which are influenced by the environment and human behavior. The water source at the Taha Qur’an Education Park is a drilled well, this water source is close to the residents’ livestock pens which can be a source of pollution. The aim of the research is to determine the quality of clean water in the Taha Qur’an Education Park. Type of qualitative descriptive research. The population in this study was all the water taps in the Taha Qur’an Education Park. The number of samples was 2 samples. Based on Minister of Health Regulation number 32 of 2017, the results of water chemistry quality tests from the results of pH measurements on samples from Tap A were 7.5 and on samples from Tap B were 7.5, which is based on Regulation of the Minister of Health of the Republic of Indonesia Number 32 of 2017. Quality standard values for pH it is 6.5-8.5, while for checking Detergent levels in clean water the results obtained for tap A samples are 0.03 Mg/L and for Tap B samples it is 0.02 Mg/L, which is based on the Minister of Health Regulation Republic of Indonesia Number 32 of 2017 The quality standard value for Detergents is 0.05 Mg/L. It is hoped that the management of the Taha Qur’an Education Park will continue to maintain the quality of clean water in the Taha Qur’an Education Park, Bima Regency.